IMPACT OF POULTRY GROWTH STAGES ON TOXIC COMPOUNDS FORMATION DURING CHARCOAL GRILLING. (International Journal of NeuroOncology and Therapeutics, 2025)
Poultry is a widely consumed source of protein, with commercial production supplying chickens of varying weights to meet market demands. However, high-temperature cooking methods, such as charcoal grilling, have been associated with the formation of toxic Compounds, including polycyclic aromatic hydrocarbons (PAHs) and heterocyclic amines (HCAs). This study aimed to evaluate the impact of grilling on toxic Compounds formation in poultry of different weight categories. Chicken breast samples were categorized into three groups (A1, A2, A2+ as un-grilled and B1, B2, B2+ as grilled) and analyzed using High-Performance Liquid Chromatography (HPLC) and Gas Chromatography-Mass Spectrometry (GC-MS). Results showed a significant increase in chromatographic peak areas after grilling, indicating the formation of potential toxic Compounds. The highest percentage increase (554%) was observed in the lowest weight category (A1 to B1), whereas the lowest increase (66%) was seen in A2 to B2. This suggests that the chemical composition and growth stage of poultry influence the extent of toxic Compounds formation during grilling. GC-MS analysis further identified specific compounds related to these changes. The findings highlight the potential health risks associated with grilling poultry, emphasizing the need for controlled cooking methods to minimize exposure to harmful toxic Compounds. Future research should focus on alternative cooking techniques and risk mitigation strategies to enhance food safety.